A Methodology for RF modeling of packages with external pin measurements. Issue 6 (11th April 2014) - Ballicchia, Mauro; Farina, Marco; Morini, Antonio; Turchetti, Claudio; Orcioni, Simone
ABSTRACT This article presents a methodology that allows the determination of the matrix representation of a package. The methodology is based on a set of calibration measurements, picked up at the external pins of the package, of a set of known integrated circuits. The representation of the package can be used both for a correct measurement of the embedded devices and to improve the design of integrated circuits. The effectiveness of the technique is demonstrated by the de‐embedding of a packaged passive integrated inductor and the design of a low noise amplifier. The measurement sets were obtained through computer simulations. The effects of added noise on data, like measurement errors, are also investigated, and an approximate methodology, able to reduce these effects, is suggested. © 2014 Wiley Periodicals, Inc. Int J RF and Microwave CAE 24:623–634, 2014.